HUBUNGAN GAYA KEPEMIMPINAN DAN MOTIVASI DENGAN KINERJA KARYAWAN DI PT. BINA VALASINDO JAKARTA - Tobing, Suzanna Josephine; Sebayang, Monica Sri Christine; Regina, Desideria (Universitas Kristen Indonesia, 2016)
This research investigates the relation between Leadership style and Motivation with Employee Performance in PT. Bina Valasindo Jakarta, one of the few competitive money changer companies in Jakarta. A sample of 60 respondents were interviewed using questionnaire with simple random sampling methods. The spearman rank correlation was used to test the three hypothesis that guided the research. The result obtained from the analysis showed that there existed relation between Leadership Style and Motivation with Employee Performance. The research reveals that leadership style and motivation given to workers in an organization has a significant influence on the workers performance. The researcher therefore suggests that the company pays more attention on the effective leadership style used and the motivation given to their employees by fullfiling their basic needs, carrier enhacement needs, giving insentive (financial or nonfinancial), bonus and other benefits.Keywords: Human Resource, Leadership, Motivation, and Performance